Research of reagent interaction on induction time during bubble–particle interaction. Issue 4 (3rd April 2023) - Cheng, Yali; Min, Fanfei; Li, Hui; Chen, Jun; Fu, Xiaoheng
ABSTRACT: This paper focuses on the influence of reagent interaction on induction time in the process of bubble–particle interaction. Induction time instrument was used to investigate the influence of single reagent and reagent interaction on induction time. Meanwhile, the influence mechanism of reagent interaction on coal particle surface wettability, surface tension, and surface functional groups was studied combined with contact angle and FTIR. The results showed that when the collector interacted with the frother, the addition of the frother reduced the induction time and increased the hydrophobicity of the coal particle surface. Compared with raw coal, the surface contact angle of collector-frother-reacted coal particles increased, and its change law was inconsistent with that of collector-reacted coal particles. The larger the contact angle, the lower the surface tension, the higher the interfacial surface tension between coal particles and water, the lower the wettability and the more hydrophobic the particle surface. FTIR spectra indicated that the influence of collector–frother interaction on the surface functional groups of coal particles was mainly reflected in the absorption peaks at 3436 cm −1 and 1400 1000 cm −1 . The effect of interaction varied with the structure of the reagent. 2-Octanol can produce multi-point adsorption on the surface of coal particles and promote the hydrophobic modification of coal particle surface. When ether alcohols interacted with arene, reverse adsorption occurred. Throughout this study, the mechanism affecting the adhesion characteristics of coal particles and bubbles caused by reagent interaction was clarified.